Silver nanoparticles modulate mitochondrial dynamics and biogenesis in HepG2 cells. (January 2020) - Li, Jiangyan; Zhang, Bangyong; Chang, Xiaoru; Gan, Junying; Li, Wenhua; Niu, Shuyan; Kong, Lu; Wu, Tianshu; Zhang, Ting; Tang, Meng; Xue, Yuying
Abstract: Silver nanoparticles (AgNPs) are inevitably released into the environment owing to their widespread applications in industry and medicine. The potential of their toxicity has aroused a great concern. Previous studies have shown that AgNPs exposure in HepG2 cells is primarily related to the damage of mitochondria, which includes induction of mitochondrial swelling and increase of intracellular levels of reactive oxygen species (ROS), the collapse of mitochondrial membrane potential and induction of apoptosis through a mitochondrial pathway. In this study, the effects of AgNPs exposure in HepG2 cells on mitochondrial dynamics and biogenesis were investigated. AgNPs were found to induce mitochondrial morphological and structural alterations. The expressions of key proteins (Drp1, Fis1, OPA1, Mff, Mfn1, and Mfn2) related to mitochondrial fission/fusion event were changed. Especially the expression of fission-related protein 1 (p-Drp1) (Ser616) was significantly up-regulated, whereas the expression of mitochondrial biogenesis protein (PGC-1α) was reduced in AgNP-treated cells. Concomitantly, the expression of autophagy marker proteins (LC3B and p62) was increased. The results suggested that AgNPs could trigger cytotoxicity by targeting the mitochondria, resulting in the disruption of mitochondrial function, damage to the mitochondrial structure and morphology, interfering in mitochondrial dynamics and biogenesis. The mitochondria could be a critical target of AgNPs in cells. The functions of mitochondria could be used for assessing the cytotoxic effects associated with AgNPs in cells. Graphical abstract: Image 10850 Highlights: AgNPs entered mitochondria in HepG2 cells. AgNPs perturbed mitochondrial dynamics, characterized by a fission phenotype. AgNPs inhibits the expression of mitochondrial biogenic PGC-1α. AgNPs induce autophagy and induce apoptosis through a mitochondrial death pathway. Abstract : Summarization of the main finding : This study investigated the mechanisms of mitochondrial damage induced by AgNPs exposure in HepG2 cells. The results suggested that the mitochondria could be a critical target of AgNPs in cells. AgNPs altered mitochondrial dynamics and biogenesis, induced autophagy and mitochondria-dependent apoptosis.